Upregulation of neuronal kynurenine 3-monooxygenase mediates depression-like behavior in a mouse model of neuropathic pain - Laumet, Geoffroy; Zhou, Wenjun; Dantzer, Robert; Edralin, Jules D.; Huo, XiaoJiao; Budac, David P.; O'Connor, Jason C.; Lee, Anna W.; Heijnen, Cobi J.; Kavelaars, Annemieke (Brain, behavior, and immunity, 2017)
•Nerve injury induces depression and upregulates kynurenine 3-monoxygenase (KMO) expression and activity.•KMO is upregulated in neurons in the contralateral hippocampus and not in microglia.•Upregulation of KMO is downstream of cerebral interleukin-1 signaling.•Inhibition of brain KMO reverses depression but not allodynia after nerve injury. Pain and depression often co-occur, but the underlying mechanisms have not been elucidated. Here, we used the spared nerve injury (SNI) model in mice to induce both neuropathic pain and depression-like behavior. We investigated whether brain interleukin (IL)-1 signaling and activity of kynurenine 3-monoxygenase (KMO), a key enzyme for metabolism of kynurenine into the neurotoxic NMDA receptor agonist quinolinic acid, are necessary for comorbid neuropathic pain and depression-like behavior. SNI mice showed increased expression levels of Il1b and Kmo mRNA in the contralateral side of the brain. The SNI-induced increase of Kmo mRNA was associated with increased KMO protein and elevated quinolinic acid and reduced kynurenic acid in the contralateral hippocampus. The increase in KMO-protein in response to SNI mostly took place in hippocampal NeuN-positive neurons rather than microglia. Inhibition of brain IL-1 signaling by intracerebroventricular administration of IL-1 receptor antagonist after SNI prevented the increase in Kmo mRNA and depression-like behavior measured by forced swim test. However, inhibition of brain IL-1 signaling has no effect on mechanical allodynia. In addition, intracerebroventricular administration of the KMO inhibitor Ro 61-8048 abrogated depression-like behavior without affecting mechanical allodynia after SNI. We show for the first time that the development of depression-like behavior in the SNI model requires brain IL-1 signaling and activation of neuronal KMO, while pain is independent of this pathway. Inhibition of KMO may represent a promising target for treating depression.